Regulation of Complement Activation by Heme Oxygenase-1 (HO-1) in Kidney Injury - Maria G. Detsika; Elias A. Lianos (MDPI AG, 2021)
Heme oxygenase is a cytoprotective enzyme with strong antioxidant and anti-apoptotic properties. Its cytoprotective role is mainly attributed to its enzymatic activity, which involves the degradation of heme to biliverdin with simultaneous release of carbon monoxide (CO). Recent studies uncovered a new cytoprotective role for heme oxygenase-1 (HO-1) by identifying a regulatory role on the complement control protein decay-accelerating factor. This is a key complement regulatory protein preventing dysregulation or overactivation of complement cascades that can cause kidney injury. Cell-specific targeting of HO-1 induction may, therefore, be a novel approach to attenuate complement-dependent forms of kidney disease.